Thalamic dopaminergic neurons projects to the paraventricular nucleus-rostral ventrolateral medulla/C1 neural circuit - Ogundele, Olalekan M. (Anat Rec (Hoboken), 2017)
Paraventricular nuclei (PVN) projections to the rostral ventrolateral medulla (RVLM)/C1 catecholaminergic neuron group constitute the pre-autonomic sympathetic center involved in the neural control of systemic cardiovascular function. However, the role of extra-hypothalamic and thalamic dopaminergic inputs in this circuit remains underexplored. Using retrograde neuroanatomical tracing and high contrast confocal imaging methods, we investigated the projections and morphology of the discrete thalamic dopaminergic neuron groups in the dorsal hypothalamic area (DHA) and their contribution to the PVN-RVLM neural circuit. We found that dopaminergic (DA) neuron sub-groups in the Zona Incerta (Zi; 60%) and Reuniens thalamic nuclei (Re; 40%) were labeled comparably to the PVN (85%) after a retrograde tracer was injected into the RVLM/C1 (p<0.01 mean±SEM). The Re/Zi DA neuron sub-groups were characterized by angulated cell bodies, superiomedial and inferiomedial projections reaching the contralateral Re/Zi and ipsilateral PVN DA neurons respectively. Ultimately, we deduced that the dopaminergic projections of the Re/Zi to the PVN contribute to the PVN-RVLM/C1 neural circuit. As a result of these connections, the Re/Zi dopaminergic neuron groups may regulate preautonomic sympathetic events associated with the PVN-RVLM pathway.